Improving the technical product knowledge of the sales agents of a family business - Yuquico, Ryan (Animo Repository, 2020)
The main focus of this Integrative Action Research paper is to improve the product knowledge and training program for our company‟s sales agents and staff. This has provided resolution to the main issue which is the lack of technical expertise and product knowledge among our sales agents. It is our desire to motivate our sales team to get moving and be motivated to learn more and improve sales performance by increasing work engagement and training opportunities. With collaboration amongst the senior management and our sale agents, the objectives of this action research have been realized. Through the use of personal interviews, surveys and the use of action research tools, my co-researchers and I were able to work together and communicate better to plan and execute interventions to addressing the main issue. I have learned that our sales agents play a big part in generating revenues for our company and it is important to invest in their development and training. I have also learned how important collaboration and teamwork is to get things done which contribute to the company‟s success.